The relationship between sleep duration, sleep quality and dietary intake in adults - Çakir, Biriz; Nişancı Kılınç, Fatma; Özata Uyar, Gizem; Özenir, Çiler; Ekici, Emine Merve; Karaismailoğlu, Eda (Springer Science and Business Media LLC, 2019)
To determine the relationship of specific macro- and micro-nutrients and food groups with sleep duration and sleep quality in adults. This cross-sectional descriptive study was conducted on 2446 adults aged between 20 and 64 years in Turkey. The participants’ socio-demographic characteristics, anthropometric measurements, and dietary intake (24-h recall) were taken. The Pittsburgh Sleep Quality Index was used to assess sleep quality. In the study, 48.9% of the participants were male and 51.1% were female, with an average age of 38.7 ± 12.70 years. Total protein, meat, and processed meat product consumption rates of long sleepers were found to be lower than those of normal sleepers (p < 0.05). Saturated fat intake of short sleepers was higher than that of long sleepers (p < 0.018). Participants with good sleep quality were found to consume higher carbohydrate, fiber, beta-carotene, vitamin E, thiamine, vitamin B6, total folate, vitamin C, calcium, magnesium, potassium, and iron compared to those with poor sleep quality (p < 0.05). When examined in terms of food groups, fruit consumption was higher in individuals with good sleep quality compared to those with poor sleep quality (p < 0.05). In this study, some macro- and micro-nutrients of the diet were found correlated with sleep duration and quality. Mechanisms mediating the relationship between sleep duration and dietary intake are multi-factorial. Because of the differences in appetite-related hormones, such as leptin and ghrelin, and hedonic factors, future studies will benefit from assessing sleep duration/quality and dietary intake.
Keywords: Sleep duration; Food groups; Dietary nutrients; Sleep quality; Anthropometric measurements; 2. Zero hunger; 16. Peace & justice; 3. Good health